Species accumulation curve of a coastal hill forest in Peninsular Malaysia - Ibrahim, Faridah Hanum; Abdul Kudus, Kamziah; Abdul Ghani, Awang Noor (Jabatan Perhutanan Semenanjung Malaysia, 2010)

(untitled)
Sampling tree diversity in a tropical forest is often very laborious and costly. With 16 different forest types present in Malaysia, it is deemed necessary to have the minimum sampling size determined for each of these forest types. This paper reports the findings on one of these forest types studies, namely coastal hill forest at Pasir Tengkorak, Langkawi. Five plots each of size 1-ha (100m x 100m) were established along a line transect. In each plot, 100 subplots each measuring 10m x 10m were further established. All trees 1cm dbh and above were enumerated, measured and identified up to the specific level. On per hectare basis there were 3414 trees/ha and 120 tree species/ha. The jackknife estimate and species area curve were applied to estimate the species richness. A total of 3414 individual trees representing 120 species, 81 genera and 31 families were recorded. Species with highest relative abundance were Swintonia sp.1, Garcinia eugnifolia and Syzygium sp.1. The jackknife estimate of species richness was 132.9 and the regression equation to estimate species richness was LnS = 2.53 + 0.24 In(A) with r2 = 96.01%. The species area curve declined as sample area increased but did not approach an asymptote at 1-ha. A minimum sampling area of 1-ha is recommended for sampling a coastal hill forest until the plot is further increased to determine its asymptote.